2011
DOI: 10.1080/09291016.2010.525380
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the time of the day and the pinealectomy on anxiety-like behaviour in male Wistar rats

Abstract: The previous studies on the anxiety-like behaviour in rats by using elevated plus maze and open field have provided rather unequivocal results because they obtained data at different times of the day. These studies have never investigated the effects of the different times of day in a single research paradigm even though the results of such studies are generally attributed to the different measurement times. Thus, we aimed to examine the effects of the time of the day and the pinealectomy on anxiety-like behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
2
2
1
Order By: Relevance
“…This assumption is in agreement with the findings of the previous studies suggesting that pinealectomy was partially involved in anxiety behavior [43,44] and seems to be coherent with another report demonstrating an important role of both maternal and postnatal pinealectomy in organization of affective behaviors in another species, in this case the Siberian hamster [43,44]. Conversely, some studies reported insignificant effect of pinealectomy which is inconsistent with our study [44]. It is likely that this disagreement would be due to the experimental conditions which are different, especially the time of the day when the measurements are performed [44] or doses and mode of Mel administration adopted [43,44].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This assumption is in agreement with the findings of the previous studies suggesting that pinealectomy was partially involved in anxiety behavior [43,44] and seems to be coherent with another report demonstrating an important role of both maternal and postnatal pinealectomy in organization of affective behaviors in another species, in this case the Siberian hamster [43,44]. Conversely, some studies reported insignificant effect of pinealectomy which is inconsistent with our study [44]. It is likely that this disagreement would be due to the experimental conditions which are different, especially the time of the day when the measurements are performed [44] or doses and mode of Mel administration adopted [43,44].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, some studies reported insignificant effect of pinealectomy which is inconsistent with our study [44]. It is likely that this disagreement would be due to the experimental conditions which are different, especially the time of the day when the measurements are performed [44] or doses and mode of Mel administration adopted [43,44]. However, a complementary experimental research is needed for illuminating the role of pineal gland in anxiety behavior.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our findings suggesting a lack of anxiety in the young adult rats with pinealectomy compared to the sham rats contradict other reports [ 28 , 29 , 30 , 31 ]. However, some crucial factors might explain the divergence in the reported effects of pinealectomy on anxiety behavior, such as age and time of testing after the removal of the pineal gland [ 31 , 32 ] and/or the hour of the day of examination [ 32 ], which determine the direction of the effects on anxiety. The depressive-like behavior associated with pinealectomy in adult rats agrees with our and other reports [ 26 , 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The closed arms were enclosed by 41-cm-tall black Plexiglas. All animals were tested by means of the procedure described by Karakas et al (2011) and Kaya et al (2011). Videotapes with Observer Software (Ethovision XT, Noldus Ethovision, Version 6) were recorded and analyzed for all anxiety-like behaviors (including distance, duration in the open arms, frequency in the closed arms, mobility, and velocity).…”
Section: Elevated Plus Mazementioning
confidence: 99%